Anithiactin D, a Phenylthiazole Natural Product from Mudflat-Derived Streptomyces sp., Suppresses Motility of Cancer Cells - Sultan Pulat; Inho Yang; Jihye Lee; Sunghoon Hwang; Rui Zhou; Chathurika D. B. Gamage; Mücahit Varlı; İsa Taş; Yi Yang; So-Yeon Park; Ahreum Hong; Jeong-Hyeon Kim; et al. (Marine Drugs, 2024)
Anithiactin D (1), a 2-phenylthiazole class of natural products, was isolated from marine mudflat-derived actinomycetes Streptomyces sp. 10A085. The chemical structure of 1 was elucidated based on the interpretation of NMR and MS data. The absolute configuration of 1 was determined by comparing the experimental and calculated electronic circular dichroism (ECD) spectral data. Anithiactin D (1) significantly decreased cancer cell migration and invasion activities at a concentration of 5 μM via downregulation of the epithelial-to-mesenchymal transition (EMT) markers in A549, AGS, and Caco-2 cell lines. Moreover, 1 inhibited the activity of Rho GTPases, including Rac1 and RhoA in the A549 cell line, suppressed RhoA in AGS and Caco-2 cell lines, and decreased the mRNA expression levels of some matrix metalloproteinases (MMPs) in AGS and Caco-2 cell lines. Thus 1, which is a new entity of the 2-phenylthiazole class of natural products with a unique aniline-indole fused moiety, is a potent inhibitor of the motility of cancer cells.